Extraction of Zr in Gold Mine Tailings to Produce TENORM Free Zirconium Oxychloride Octahidrate (ZOC) - Sari, Erlin Purwita; Sajima, Sajima; Prabasiwi, Devi Swasti; Poernomo, Herry (Indonesian Journal of Chemical Science, 2021)
Gold mine tailings causes environmental problems if disposed without previous processing. Nowadays, secondary resources recycling has become people worldwide consideration because the increasing awareness of the sustainable development urgency. This study aims to extract the valuable mineral content in gold mine tailings to produce ZOC. The research begins with an alkaline fusion process using NaOH. The water leaching process was performed to the smelted alkaline with ratio of solids mass to water volume of 1:30. The resulted solid was dried for further used in the synthesis of ZOC. A number of ZOCs were reacted with HCl at a ratio of solid mass to HCl volume of 1:20, HCl 4N, and temperature of 60 Â°C for 1.5 hours. The solution then be crystallized to obtain ZOC solids without centrifugation process. This reaction was done using 1-step ZOC synthesis method without passing over zirconium base sulfate (ZBS) manufacturing phase. The ZOC crystals were analyzed using FTIR, XRD, and XRF. The data indicated that the synthesized product was identified as zirconium oxychloride octahydrate (ZrOCl2Â·8H2O). The compound showed 0% of ThO2 and U3O8 content or could be called TENORM free. The calculation results showed that the % recovery of Zr was 85.94%.